ANALISA SIFAT MEKANIK KOMPOSIT UJI BENDING - Junaidi, Junaidi; Ritonga, Din Aswan Amran (JiTEKH, 2020)
In this study, the material used was coconut husk fiber with a straight fiber orientation direction with different volume fractions with alkali treatment (NaOH) for two hours and without treatment using Polyester BQTN 157 as the matrix. Manufacture by printing in printed, bending testing carried out with reference to ASTM D 6110 standard. The purpose of this study was to determine the optimal bending strength of coconut coir fiber composites at volume fractions 0% fiber 100% resin, 10% fiber 80% resin, 20% fiber 80% resin, 30% fiber 70% resin, 40% fiber 60% resin, 50% resin 50% fiber, 60% resin 40% fiber and 70% fiber 30% resin with alkaline treatment (NaOH) for two hours and without treatment and find out the fracture results in specimens that have optimal prices from bending testing. The results of composite testing of coconut coir fiber without treatment with volume fraction variations with bending testing obtained the average bending elasticity modulus at Vf 60% resin 40% fiber with a value of 619047.619 MPa. And the test results with alkali treatment (NaOH) obtained the average bending elasticity modulus at Vf 70% resin 30% fiber with a value of 4893.410928 MPa. The observation of fault results obtained the type of broken fiber fault